PENGARUH JENIS PENGEMAS DAN SUHU PENYIMPANAN TERHADAP KARAKTERISTIK ADONAN SATE LILIT (LULUH) - Sri Mastini, Luh Putu Widia; Hartiati, Amna; Mulyani, Sri (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2015)
The study aim to 1) know the effect of packaging type and temperature storage of dough satay (luluh) based on some characteristics, 2) determine the best of packaging type and temperature storage to get dough satay (luluh) with the best shefl life based on some characteristics. This research used Randomized Block Design with two factors. The first factor was packaging type that consisted of three level of plastic namely ; polypropilen, polyethylen, and mixed plastic of polyethylen and poliamide plastic. The second factor was temperature storage that consisted of three type namely : (25 ± 2 o C), ( 10 ± 2 o C ), and (-5 ± 2 o C ). Research result showed that storage temperature significantly effect of dough satay (luluh) free fatty acids and total microbial, while type of packaging significantly effect of dough satay (luluh) free fatty acids in two and three days storage, but nonsignificantly effect of the total microbial, interaction of packaging type and temperature storage nonsiginifacantly effect of dough satay (luluh)total microbial, but significantly effect of dough satay (luluh) free fatty acids. Storage with type of plastic with two layers Polyethylen and nylon plastic packaging at ( -5 ± 2 o C ) was the best treatment for extend of dough satay (luluh) shelf life with the best shelf life of dough satay (luluh) was 3 days. Keyword :Dough satay, (luluh), packaging type, temperature storage, shelf life
Keywords: 67